Kajian Kelayakan Kecamatan Salahutu Sebagai Calon Ibu Kota Kabupaten Kepulauan Ambon - Layn, Usman Gumanti; Botanri, Adnan Affan Akbar; Berhitu, Pieter Th (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The issue of territorial expansion that has been discussed in Maluku is about the division of Leihitu and Salahutu sub-districts into a new regency named Ambon Islands Regency. Problems that occur such as the difficulty of administrative management such as identity cards, the lack of supporting facilities for settlement activities, the distance between the sub-district control and the Regency Capital, and various other problems that occur. The purpose of this study is to determine the feasibility of Salahutu District to become a candidate for the New Autonomous Region of the Ambon Islands Regency as well as a suitable location to become the center of its capital city. This research uses qualitative methods with data collection techniques through direct surveys. The analysis used is human development index analysis, land suitability analysis and population density analysis. The results obtained are the human development index in Salahutu District, which is 61.99, which means that the category is medium / middle to upper. Then for the cultivation area, there are 14,409 ha or 98.94% of the total area of Salahutu District, so there is still plenty of room for construction and development of infrastructure and facilities. For the center of the capital city, the results were obtained that Tulehu State became a priority or the top choice because it had the highest density level of 10.44 people / ha. The importance of the results of this research is as a basis for the expansion of new sub-districts in Central Maluku Regency based on problems that have occurred to create plans that are beneficial to the community